A Feasibility Study of the Addition of STEPPS in Outpatients With Bipolar Disorder and Comorbid Borderline Personality Features: Promises and Pitfalls - Georg Riemann (Frontiers Media S.A., 2021)
Background: Pharmacotherapy is a cornerstone in bipolar disorder (BD) treatment whereas borderline personality disorder (BPD) is treated primarily with psychotherapy. Given the overlap in symptomatology, patients with BD may benefit from psychotherapy designed for BPD.Aims: This paper reports the findings of a non-controlled open feasibility study of STEPPS training in patients with BD and borderline personality features (BPF).Methods: Outpatients with BD were screened for BPD, and if positive interviewed with SCID-II. Patients with at least three BPF, always including impulsivity and anger burst, were included in the intervention study. Severity of BD and BPD and quality of life were assessed. Descriptive statistics were performed.Results: Of 111 patients with BD 49.5% also screened positive on BPD according to PDQ-4+, and 52.3% of these had BPD according to SCID-II. Very few participants entered the intervention study, and only nine patients completed STEPPS. Descriptive statistics showed improvement on all outcome variables post treatment, but no longer at 6-month follow up. We reflect on the potential reasons for the failed inclusion.Conclusion: Features of BPD were highly prevalent in patients with BD. Still, recruiting patients for a psychological treatment originally designed for BPD proved to be difficult. Feedback of participants suggests that the association of STEPPS with “borderline” had an aversive effect, which may have caused limited inclusion for screening and subsequent drop-out for the treatment. Therefore, STEPPS should be adapted for BD to be an acceptable treatment option.Clinical Trial Registration:www.ClinicalTrials.gov/3856, identifier: NTR4016.